Eggshell penetration by Salmonella Typhimurium in table eggs: Examination of underlying eggshell structures by micro-computed tomography and scanning electron microscopy. (December 2015) - Ray, Aaron; Roberts, J.R.; Flavel, R.; Chousalkar, K.K.
Abstract: Horizontal infection of table eggs by food borne, human infection causative agents such as Salmonella is a serious concern for consumers and industry. In this study, we investigated the relationship between eggshell translucency, mammillary layer abnormalities and pore structure using Computed Tomography (CT) and scanning electron microscopy. The effects of eggshell pore structure, size and number on Salmonella Typhimurium penetration was also investigated. The eggs were infected with S. Typhimurium and were incubated at 37 °C for 3 or 6 days. Micro CT results comparing shell features to shell translucency found that there was a significantly increased incidence of externally branching pores found in the high translucency score eggshell group, and more straight pores found in the low translucency score group. Different pore structures, the total number of pores and the shell thickness do not appear to play a role in the horizontal infection of eggs by the S. Typhimurium strain used in this study. While it is likely that the presence of shell pores is responsible for shell penetration, other unknown shell factors must also play a role, and eggshells with a higher incidence of shell pores are not penetrated at a higher rate. Highlights: Micro CT permitted the viewing of a 3 dimensional model of the shell's palisade layer. Micro CT has allowed the detection of externally and internally branching pores in shells. Externally branching pores increased with high eggshell translucency. Straight pores were found in the egg shells with low translucency. Pore structures and numbers do not play a role in transmission of Salmonella Typhimurium.